URGENSI PP NOMOR 24 TAHUN 2010 DALAM PENCEGAHAN PEMBUKAAN LAHAN PERKEBUNAN SECARA ILEGAL DI KAWASAN HUTAN PRODUKSI: The urgency of Government Regulation of the Republic of Indonesia Number 24 of 2010 concerning the Use of Forest Areas in Preventing Illegal Plantation Land Clearing in Production Forest Arease - Galgani, Malino Gemma (Jurnal Globalisasi Hukum., 2025)
This study examines the implementation of Government Regulation No. 24 of 2010 concerning the Use of Forest Areas as a preventive measure against illegal plantation land clearing within production forest zones. These forest areas, which are designated for sustainable use, are frequently subjected to unauthorized land conversion by corporate entities and individuals lacking official permits, thereby threatening ecosystem sustainability and causing significant state losses. Employing a normative juridical approach and case studies, the research reveals that, despite the Regulation providing a clear legal framework, its enforcement faces substantial challenges, including weak oversight, overlapping authorities, and inadequate law enforcement. The Ministry of Environment and Forestry (KLHK), in collaboration with regional governments, is expected to play an active role in supervising and issuing Forest Area Borrow-and-Use Permits (IPPKH). The study concludes that the effectiveness of this policy heavily relies on inter-agency synergy, strengthening regional institutional capacities, and fostering community participation in monitoring activities. Systemic reforms are necessary to optimize the Regulation's function as a sustainable instrument for forest protection.